2023
DOI: 10.1007/s11948-022-00419-9
|View full text |Cite
|
Sign up to set email alerts
|

Socially Assistive Devices in Healthcare–a Systematic Review of Empirical Evidence from an Ethical Perspective

Abstract: Socially assistive devices such as care robots or companions have been advocated as a promising tool in elderly care in Western healthcare systems. Ethical debates indicate various challenges. An important part of the ethical evaluation is to understand how users interact with these devices and how interaction influences users’ perceptions and their ability to express themselves. In this review, we report and critically appraise findings of non-comparative empirical studies with regard to these effects from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…To answer this question, we used the subset of comparative studies from a comprehensive review of empirical evidence on human-machine interaction with SATs in healthcare. The results from the arm of non-comparative studies were reported elsewhere [ 5 ]. The review protocol was designed and agreed upon by the authors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To answer this question, we used the subset of comparative studies from a comprehensive review of empirical evidence on human-machine interaction with SATs in healthcare. The results from the arm of non-comparative studies were reported elsewhere [ 5 ]. The review protocol was designed and agreed upon by the authors.…”
Section: Methodsmentioning
confidence: 99%
“…These technologies, which include care robots, smart screen assistants, virtual avatars, and companion devices can be characterized by entailing at least three essential features. Firstly, they integrate into the everyday lifeworld of their users [ 4 , 5 ]. Secondly, they offer support by taking over control, routine, or steering tasks or by acting with or on behalf of their users [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conducted through focus group interviews with 97 individuals, averaging 75 years old, a study revealed that elderly users frequently express a strong inclination toward determining the information monitored and stored by robots, advocating for a selective approach to maintain control and safeguard privacy in the realm of robotic assistance 12 . Furthermore, there is often a lack of awareness among both the elderly and their caregivers regarding constant behavioral monitoring and the potential sharing of these records with third parties 83 .…”
Section: Impacts Of Using Eldercare Robotsmentioning
confidence: 99%